HUBUNGAN ANTARA DAYA LEDAK OTOT LENGAN DENGAN PRESTASI TOLAK PELURU GAYA MENYAMPING PADA SISWA KELAS VI SD NEGERI 2 SURO KECAMATAN KALIBAGOR BANYUMAS - Kuryanto, Kuryanto (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2016)
The research was concuted with the aims to find out the correlation between the biceps explosive power and shot-put achievement of sideways style of the students class VI SD Negeri Suro Kalibagor Banyumas. The aims expected were (1) theoretically, it increased the knowledge of sport especially shot-put, (2) practically; it was benefical for sport teacher, especially the trainer of shot-put to plan and conduct a good rehearsal program. This research was correlational research, the subjects were the sixth graders of SD NegeriSuroKalibagorBanyumas with 30 students. The instrument and the technique used in this research was test and the measurement of biceps explosive power and the test of shot-put of sideways style. The data analysis was by correlation test with the significance level 5%. The result showed that there was a significant correlation between the biceps explosive power and shot-put achievement of sideways style of the students class VI SD NegeriSuroKlibagorBanyumas. It could be seen from the result of the coefficient correlation, that was rcount0,676 >rtabel0,361